Diseases affecting cassava - Legg, James P.; Álvarez, Elizabeth (Burleigh Dodds Science Publishing Limited, 2017)
Cassava diseases are major production constraints wherever the crop is grown. Although diseases will continue to pose a challenge to cassava producers in the immediate future, tremendous progress is being made in developing control tactics. These range from biotechnological approaches for enhancing disease resistance to viruses to the application of biocontrol suppressors that help cassava plants resist infection from soil-dwelling fungal pathogens, and initiatives to enhance global cooperation in the implementation of robust phytosanitary measures preventing the spread of pathogens to previously unaffected territories. In this chapter, we describe the characteristics of some of the key diseases of cassava, highlight methods that are currently being applied to control them and discuss some of the promising new areas for research on cassava disease control.